Toxic effects of leaves of Ricinus communis (Euphorbiaceae) to laboratory nests of Atta sexdens rubropilosa (Hymenoptera: Formicidae) - Hebling, Maria José A. [UNESP]; Maroti, Paulo Sérgio [UNESP]; Bueno, Odair Correa [UNESP]; Da Silva, Osvaldo Aulino [UNESP]; Pagnocca, Fernando Carlos [UNESP] (Cambridge University Press (CUP), 1996)
Laboratory nests of the leaf-cutting ant Atta sexdens rubropilosa Forel fed daily with leaves of Ricinus communis showed a gradual decrease in fungal garden volume, a higher ant mortality rate, and fungal garden extinction after 6 weeks. The mean oxygen consumption rate of these ants was higher than that of control ants collected from nests fed with leaves of Eucalyptus alba (Myrtaceae) suggesting one or more components of the leaves of R. communis had a direct physiological effect on the ants, in addition to inhibiting fungal garden growth.